Afflicted : How Vulnerability Can Heal Medical Education and Practice - Piemonte, Nicole M. (Book collections on Project MUSE., 2018)
While many commentators have pointed to the lack of compassion and empathy in medicine, their critiques, for the most part, have not considered seriously the deeper philosophical, psychological, and ontological reasons why clinicians and medical students might choose to conceive of medicine as an endeavor concerned solely with the biological workings of the body. Thus, this book examines why it is that existential suffering tends to be overlooked in medical practice and education, as well as the ways in which contemporary medical epistemology and pedagogy not only perpetuate but are indeed shaped by the human tendency to flee from the reality of death and vulnerability. It also explores how students and doctors perceive medicine, including what it means to be a doctor and what responsibilities doctors have toward addressing existential suffering. Contending that the being of the physician is constituted by the other who calls out to her in his suffering, this book argues that the doctor is, in fact, called to attend to suffering that extends beyond the biological. It also discusses how future physicians might be "brought back to themselves" and oriented toward a deeper sense of care through a pedagogy that encourages intentional reflection and values the cultivation of the self, openness to vulnerability, and a fuller conception of what it means to be a healer.